A New You In 21 Days: Shortcuts to Losing Weight, Looking Good and Feeling Great - Kate Shapland
A guide to exercise, diet and beauty for women, with the emphasis on how to change your appearance for the better in just three weeks and how to improve health and looks permanently. The book is in three exercise; diet, with 50 calorie-counted recipes; and feminine beauty, with step-by-step instructions on how to apply make-up.